Program for the Promotion of Children’s Socio-cognitive development Part 2: Parents Intervention - Lucas, Carla Vale; Soares, Maria Luísa Pereira (Revista de Psicologia da IMED, 2014)
The social cognition is very important for a successful social interaction, and thus for the psychosocial balance of individuals. It is considering the importance of such, that one program was created to promote the children’s social-cognitive development, which focuses on moral resilience and social competence. Two groups, in parallel intervention, were attended in this program: parents with children up to 12 years and children from 7 to 12 years. The intervention modules for parents were addressed with greater emphasis, answering questions like: "What impact does the interactions and experiences offered by the people closest to the child have in his/her development and how it is possible to maximize their potential?”